Linking the morphology of fluvial fan systems to aquifer stratigraphy in the Sutlej‐Yamuna plain of northwest India. Issue 2 (3rd February 2016) - van Dijk, W. M.; Densmore, A. L.; Singh, A.; Gupta, S.; Sinha, R.; Mason, P. J.; Joshi, S. K.; Nayak, N.; Kumar, M.; Shekhar, S.; Kumar, D.; Rai, S. P.
Abstract: The Indo‐Gangetic foreland basin has some of the highest rates of groundwater extraction in the world, focused in the states of Punjab and Haryana in northwest India. Any assessment of the effects of extraction on groundwater variation requires understanding of the geometry and sedimentary architecture of the alluvial aquifers, which in turn are set by their geomorphic and depositional setting. To assess the overall architecture of the aquifer system, we used satellite imagery and digital elevation models to map the geomorphology of the Sutlej and Yamuna fan systems, while aquifer geometry was assessed using 243 wells that extend to ∼200 m depth. Aquifers formed by sandy channel bodies in the subsurface of the Sutlej and Yamuna fans have a median thickness of 7 and 6 m, respectively, and follow heavy‐tailed thickness distributions. These distributions, along with evidence of persistence in aquifer fractions as determined from compensation analysis, indicate persistent reoccupation of channel positions and suggest that the major aquifers consist of stacked, multistoried channel bodies. The percentage of aquifer material in individual boreholes decreases down fan, although the exponent on the aquifer body thickness distribution remains similar, indicating that the total number of aquifer bodies decreases down fan but that individual bodies do not thin appreciably, particularly on the Yamuna fan. The interfan area and the fan marginal zone have thinner aquifers and a lower proportion of aquifer material, even in proximal locations. We conclude that geomorphic setting provides a first‐order control on the thickness, geometry, and stacking pattern of aquifer bodies across this critical region. Key Points: Alluvial channel deposits form important but laterally disconnected aquifers in fans Geomorphic setting provides a first‐order control on spatial distributions of aquifer bodies Persistent channel positions results in thick aquifers, likely composed of multistoried sand bodies